Synthesis, characterization and band gaps of ZnO, Zn(1-x) CuxO and Zn(1-x)MnxM nanomaterials / Muhd Firdaus Kasim - Kasim, Muhd Firdaus (Institute of Graduate Studies, UiTM, 2015)
The structural and optical properties of ZnO can be modified by doping. The most important issue in this research is band gap. This is because band gaps of materials can be the criteria for its usage in various device applications. The motivation for this research is to obtain substitutionally doped ZnO with various band gap values. This will enhance the light absorption properties of the modified materials. Modified ZnO materials can be used in future applications such as solar cells, gas sensors, optoelectronic devices and etc with improved performance. In this work, Copper (Cu) and Manganese (Mn) will be used as dopant in ZnO nanostructures. Fundamental studies of ZnO and Cu and Mn doped ZnO were studied. Synthesis and characterization of ZnO and (TM=Cu, Mn) doped ZnO nanostructures are analysed and the relationship with their band gaps were investigated. The nanostructures were successfully synthesized via a simple solgel method without using any chelating agents…